2009
DOI: 10.1002/ffj.1930
|View full text |Cite
|
Sign up to set email alerts
|

Headspace solid‐phase microextraction and gas chromatography–olfactometry analysis of raw spirits of different organoleptic quality

Abstract: The aim of this research was to determine which compounds contribute to the flavour of agricultural distillates and to indicate those compounds which are responsible for a deterioration of sensory quality. Aroma profiling was carried out by headspace solid-phase microextraction (HS-SPME) and gas chromatography-olfactometry (GC-O). Aroma profiles were obtained using the fingerspan method. It was ascertained that the aroma profiles of agricultural distillates contain about 40 odours, some of which may serve in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Also, the influence of mycotoxin contamination in the used raw materials on the presence of aldehydes and higher alcohols was researched (Kloskowski and Mikulski, 2010). Most commonly, the SPME (Plutowska and Wardencki, 2009; Zi o»kowska and Jele n, 2012) and HS-SPME (Biernacka and Wardencki, 2012;Wardencki, 2008;Plutowska et al, 2010) techniques were employed to analyze volatile fractions. Information related to the studies of volatile compounds in Thai spirits made from sticky rice can be found in the published literature (Wechgama et al, 2008a(Wechgama et al, , 2006b.…”
Section: Downloaded By [Rutgers University] At 12:11 11 April 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the influence of mycotoxin contamination in the used raw materials on the presence of aldehydes and higher alcohols was researched (Kloskowski and Mikulski, 2010). Most commonly, the SPME (Plutowska and Wardencki, 2009; Zi o»kowska and Jele n, 2012) and HS-SPME (Biernacka and Wardencki, 2012;Wardencki, 2008;Plutowska et al, 2010) techniques were employed to analyze volatile fractions. Information related to the studies of volatile compounds in Thai spirits made from sticky rice can be found in the published literature (Wechgama et al, 2008a(Wechgama et al, , 2006b.…”
Section: Downloaded By [Rutgers University] At 12:11 11 April 2015mentioning
confidence: 99%
“…The first described group of alcohols is raw spirits, which have been analyzed mostly in order to identify their botanical characteristics (Bauer-Christoph et al, 1997;Jele n et al, 2010;Liu and Jiang, 2002;Zi o»kowska and Jele n, 2012). The matrix composition of the spirits was also investigated to detect aromatic compounds (Plutowska and Wardencki, 2009;Plutowska et al, 2010) and determine fatty acids (Plutowska and Wardencki, 2008). Also, the influence of mycotoxin contamination in the used raw materials on the presence of aldehydes and higher alcohols was researched (Kloskowski and Mikulski, 2010).…”
Section: Downloaded By [Rutgers University] At 12:11 11 April 2015mentioning
confidence: 99%
“…The same samples were analysed again by Plutowska and Wardencki with GC‐O and sensory analysis, the latter conducted by a group of three panellists. The HS‐SPME technique was used to prepare the samples prior to analysis.…”
Section: Analysis Of Agricultural Distillatesmentioning
confidence: 99%
“…The samples of the highest quality were characterized by three or four aromas, mainly nauseating, fruity/sweet, chemical/solvent and green/plant. It was established that geosmin and dimethyl trisulphide were responsible for the least pleasant smell .…”
Section: Analysis Of Agricultural Distillatesmentioning
confidence: 99%
“…In addition to conservation, alcoholic fermentation leads to a joyful aroma due to a great number of aroma compounds (Duarte et al . ) that are especially important in fruit wine, as they contribute to the quality of the final product (Pluowska and Wardencki, ). Although autochthonous yeasts are reported to produce unique flavors and exceptional quality when used for traditional wine fermentation (Fleet et al .…”
Section: Introductionmentioning
confidence: 99%